FEATURES OF STRATEGIC PLANNING IN THE OIL AND GAS INDUSTRY - A. Andabay (Academic Journal of Physical and Chemical Sciences, 2019)
In the face of increasing competition in the global energy markets, given the high importance of the oil and gas industry for the Kazakh economy, the topical issue is improving the strategic planning system in the oil and gas industry. In the article, the author examines the existing hierarchy of program documents of strategic planning in the oil and gas industry, highlights the problems inherent in the current system. The main provisions and objectives of the strategic planning of oil companies are considered. The role of the oil industry in the main macroeconomic indicators of the country’s development is shown.